El nacimiento de un monstruo - Manuel Gárate Chateau (Caravelle)
French society and its print media were specially sensitive to the Coup d’État in Chile and the dictatorship’s military repression of Allende’s government supporters. French cartoonists were not irrelevant to this phenomenon, and we assume that they were key actors in creating an universal image of Pinochet who embodied evil’s archetype according to the codes and evocations of the worst episodes in the History of twentieth century Europe. This article shows some of this route through a selection of images published between 1973 and 1990.